Electronics Diagnose for Jaundice Disease Integrated with Informative SMS Notification: Diagnose Jaundice Expert System (DIJAD) - Fazeha Nasya Abd Malik; Muhammad Thariq A Razak (International ABEC, 2021)
Medical expert system is very important nowadays to detect any disease as early as we can. Electronics Diagnose For Jaundice Disease Integrated With Informative SMS Notification: Diagnose Jaundice Expert System (DIJAD) has been designed and developed to help early detection of jaundice by identifying the symptoms statistically after diagnosing the patient, based on the information available in its database. The system is conducted to detect the type of the jaundice faster based on the initial sign or symptom of the disease. It will provide the result of diagnosing jaundice and the nearest clinic via Short Message Service (SMS) to the patient. The interview were conducted to validate the functionality and effectiveness of the DIJAD, two method is used which is user test and system function test. The result indicated that 5 random user 2 doctors agree that the system is user-friendly and easy to use. Other than that, the result from system function test. It can be concluded that the system is fully functioning, and no error occurred. This system uses Forward Chaining method. Forward Chaining is method that is driven by the data where the tracking stars from the observation of the input information and the try to describe the conclusions. DIJAD developed using Hypertext Preprocessor (PHP) for the programming language in conjunction with MySQL as a database system. The outcome of DIJAD able to facilitate community in diagnose early jaundice disease that can save time and give positive impact in our effort to prevent jaundice to become worst.